2017
DOI: 10.1021/acs.jpcc.7b01475
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mg-Doping Site Control in the Performance of Li4Ti5O12 Li-Ion Battery Anode: First-Principles Predictions and Experimental Verifications

Abstract: Li4Ti5O12 (LTO) has attracted tremendous attention as a stationary Li-ion battery anode material due to its excellent stability. However, the poor rate capability caused by the low electrical conductivity limits its practical use. Previously, Mg-doping in LTO has been used to improve the electrical conductivity and electrochemical properties, but the Mg-doped LTO system generally exhibits large anomalies in the electrical properties and capacities, which limits the reliable mass-production of engineered LTO. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Figure 12a shows the initial charge−discharge curves of pure and W-doped LTOs at a current density of 1 C in the voltage range of 1−3 V. At 1 C, initial discharge capacity of phase-pure 1.5−2 μm LTO particles is 120 mAh/g (Figure 12a), which is comparable to values reported for the micron size solid-state synthesized LTO system. 12,69 Whereas, for W-doped particles initial discharge capacities increase to 139, 133, 130, and 128.4 mAh/g for x ∼0.05, 0.10, 0.15, and 0.20, respectively. Flat plateaus in the voltage versus capacity curves (Figure 12a) around 1.53 V/1.61 V correspond to the discharge/charge process, respectively, based on the Li-ion intercalation/deintercalation into the respective crystal structures accompanied by Ti 4+ /Ti 3+ redox reactions.…”
Section: Electrochemical Characterization Methodmentioning
confidence: 98%
“…Figure 12a shows the initial charge−discharge curves of pure and W-doped LTOs at a current density of 1 C in the voltage range of 1−3 V. At 1 C, initial discharge capacity of phase-pure 1.5−2 μm LTO particles is 120 mAh/g (Figure 12a), which is comparable to values reported for the micron size solid-state synthesized LTO system. 12,69 Whereas, for W-doped particles initial discharge capacities increase to 139, 133, 130, and 128.4 mAh/g for x ∼0.05, 0.10, 0.15, and 0.20, respectively. Flat plateaus in the voltage versus capacity curves (Figure 12a) around 1.53 V/1.61 V correspond to the discharge/charge process, respectively, based on the Li-ion intercalation/deintercalation into the respective crystal structures accompanied by Ti 4+ /Ti 3+ redox reactions.…”
Section: Electrochemical Characterization Methodmentioning
confidence: 98%
“…Therefore, the charge carrier concentration is greatly improved, and then the electronic conductivity of LTO is effectively improved. Lee et al 104 also demonstrated that the conductivity of LTO can be increased by Mg doping. A combination Reproduced with permission.…”
Section: Influence Of Doping On Electron Conductionmentioning
confidence: 96%
“…Therefore, the charge carrier concentration is greatly improved, and then the electronic conductivity of LTO is effectively improved. Lee et al 104 also demonstrated that the conductivity of LTO can be increased by Mg doping. A combination of thermodynamic modeling and DFT calculations exhibited that decreasing annealing temperatures for Mg‐doped LTO can change the Mg‐doping sites from the paired substitutions in Li + and Ti 4+ sites in positive and negative charge states (Mg Li + ), to charge‐neutral substitution of (Mg Li 0 ).…”
Section: Improvement Of Electrochemical Performancesmentioning
confidence: 97%
“…Therefore, it is essential to consider the formation and the effects of the point defects to allow researchers precise control during synthesis. Cho et al [106] used ab initio to study the effects of charge-compensated point defects for Mg-doped LTO and its electronic properties. LTO has two metallic elements, Li and Ti; the Mg dopant can prefer only one site or occupy both sites.…”
Section: Elucidating Enhancements In Electrochemical Performancementioning
confidence: 99%
“…Schematic diagram of Mg site energetics and their corresponding density of states. Taken form Ref [106]. Total density of states X-doped LTO (X=Cr, Fe, Ni, and Mg).…”
mentioning
confidence: 99%